Differential effects of warming and acidification on chemosensory transmission and detection may strengthen non-consumptive effects of blue crab predators (Callinectes sapidus) on mud crab prey (Panopeus herbstii) - Draper, Alex M.; Weissburg, Marc J. (Frontiers in Marine Science, 2022)
Predators control prey abundance and behavior, both of which strongly influence community dynamics. However, the relative importance of these predator effects may shift with climate change stressors, suggesting understanding the potential effects on these different processes is critical to predicting effects of climate change on community function. We investigated the effects of global warming and ocean acidification on the transmission and detection of chemical cues from blue crab predators (Callinectes sapidus) by mud crab prey (Panopeus herbstii). We measured mud crab feeding rates in the presence of blue crab predator cues, using either predator cues stressed in acidified conditions or mud crabs stressed in warmed and acidified conditions. Mud crabs consumed less food in the presence of predator cues, but acidifying the cues or subjecting mud crabs receiving the cues to acidified environment did not affect this antipredator response. Mud crabs in warmed conditions consumed significantly less food regardless of predator cue, but this effect was reversed in ambient conditions. Therefore, climate change may produce shifts in community regulation as warming potentially compromises consumptive effects of predators by reducing motor function, whereas non-consumptive effects mediated by sensory transmission and detection remain unaffected by acidification. Overall, warming may have stronger effects than acidification on community dynamics in oyster reefs as global temperatures continue to rise.